An efficient routing protocol based on polar tracing function for underwater wireless sensor networks for mobility health monitoring system application. - Venkateswarulu, BalajiVijayan; Subbu, Neduncheliyan; Ramamurthy, Sivakumar (Journal of Medical Systems, 2019)
In recent times, Underwater Wireless Sensor Networks (UWSNs) have involved various applications in oceanographic data collection, pollution revealing, environmental monitoring, offshore exploration, disaster prevention, military surveillance, etc. nevertheless the unique characterization of UWSNs are designed for the grid division on geographical system with polar tracing function to attain the shortest- path and minimizing the energy consumption for end – to – end transmission. In this paper, we proposed a Grid Division Polar Tracing (GDPT) routing protocol function using greedy algorithm for reducing the energy consumption by incorporating into cubic grids and polar tracing functions. The NS2 simulation results proved that the optimal distance of the found path, packet delivery ratio, network lifetime, energy consumption and propagation delay are the performance metrics in the routing protocols. In proposed case used for application of underwater sensor based health monitoring system for wireless in under water environment.